2022
DOI: 10.1128/aac.01304-21
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftibuten/VNRX-5236 against Urinary Tract Infection Isolates of Antimicrobial-Resistant Enterobacterales

Abstract: Ceftibuten/VNRX-7145 is a cephalosporin/boronate β-lactamase inhibitor combination under development as an oral treatment for complicated urinary tract infections caused by Enterobacterales producing serine β-lactamases (Ambler class A, C and D). In vivo , VNRX-7145 (VNRX-5236 etzadroxil) is cleaved to the active inhibitor, VNRX-5236. We assessed the in vitro activity of ceftibuten/VNRX-5236 against 1,066 urinary isolates of Enterobacterales from a 2014-2016 glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Our study of recent isolates collected globally demonstrated that ceftibuten-ledaborbactam possesses potent in vitro activity (>88% of isolates were inhibited at 1 μg/mL) against ESBL-positive (CTX-M-1 group-, CTX-M-9 group-, and SHV-positive) isolates of Enterobacterales , confirming earlier reports ( 12 , 13 , 19 ). For molecularly defined ESBL-positive isolates, ceftibuten-ledaborbactam (MIC 90 , 0.25 to 2 μg/mL), imipenem (MIC 90 , 0.25 to 1 μg/mL), and meropenem (MIC 90 , 0.12 to 0.25 μg/mL) had low MICs (≤1 μg/mL) and comparable in vitro activities ( Table 2 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study of recent isolates collected globally demonstrated that ceftibuten-ledaborbactam possesses potent in vitro activity (>88% of isolates were inhibited at 1 μg/mL) against ESBL-positive (CTX-M-1 group-, CTX-M-9 group-, and SHV-positive) isolates of Enterobacterales , confirming earlier reports ( 12 , 13 , 19 ). For molecularly defined ESBL-positive isolates, ceftibuten-ledaborbactam (MIC 90 , 0.25 to 2 μg/mL), imipenem (MIC 90 , 0.25 to 1 μg/mL), and meropenem (MIC 90 , 0.12 to 0.25 μg/mL) had low MICs (≤1 μg/mL) and comparable in vitro activities ( Table 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…Ceftibuten-ledaborbactam at 1 μg/mL inhibited 89.7% of MDR isolates, compared to susceptibilities of 86.5% for imipenem-relebactam, 84.6% for meropenem, and 77.6% for imipenem. Previous studies have also reported that ceftibuten-ledaborbactam demonstrated similar potency in vitro compared to carbapenems (meropenem) and current β-lactam/β-lactamase inhibitors (meropenem-vaborbactam and ceftazidime-avibactam) against MDR Enterobacterales ( 12 , 19 ). In one recent study of 205 challenge set isolates of Enterobacterales , Mendes et al reported that ceftibuten-ledaborbactam MICs (MIC 50 , 0.12 μg/mL; MIC 90 , 1 μg/mL) were 2- to 4-fold lower than for ceftazidime-avibactam (MIC 50 , 0.5 μg/mL; MIC 90 , 2 μg/mL) ( 13 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The combination of CTB/VNRX-7154 showed similar potency level to ceftazidime-avibactam (IV) and meropenem-avibactam against Enterobacterales- producing SBLs, in in vitro studies. This combination offers an alternative path to treatment since it is readily orally available [ 55 ].…”
Section: Carbapenemase Inhibitorsmentioning
confidence: 99%